INOVASI KURIKULUM SEKOLAH HIJAU BERBASIS PERTANIAN UNTUK MENDUKUNG PEMBANGUNAN BERKELANJUTAN - Aprido, Muhamad; Abidin, Zaenal (Tahta Media Group, 2024)
This study aims to analyze the design and implementation of an agriculture-based Green School curriculum innovation to support sustainable development at MTs Ma'hadut Tholabah Babakan. The research employed a qualitative approach with a developmental case study design. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that the curriculum innovation was developed integratively based on the principles of Education for Sustainable Development (ESD), emphasizing experiential learning, cross-subject integration, and the establishment of an environmentally friendly school culture. The implementation of organic farming practices, compost management, and green entrepreneurship contributed to improving students’ environmental literacy and ecological responsibility. Despite challenges related to infrastructure and measurable evaluation systems, this curriculum innovation demonstrates significant potential in supporting the achievement of sustainable development goals within the madrasah context.